PRESEPSI MASYARAKAT TERHADAP PENCEGAHAN DEMAM BERDARAH DI WILAYAH KERJA PUSKESMAS SIAK HULU I KABUPATEN KAMPAR - Nurvi Susanti; Nofri Hasrianto; Rudini Rudini (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2018)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus that classified Athropod-Borne Virus, Aedes genus, especially aedes aegypti or aedesalbopictus. DHF may occur throughout the year, cycle of rine and can affect all age category. This disease is related wich knowladge, understanding and behavior community to the environment with health program impossible this desiase contagious to this death. Behavior is the second largest factor after the environmental factor that can affect the health of individual, groups and communities. In Siak Hulu 1 Public Health Centre, there aiare still lack of knowledge, attitudes, and role of health worker to prevention of DHF. The purpose of this study was to determine the preception of public in prevention of DHF. A design used in this research was analytic quantitative with the approach cross sectional. Population in this study is Pandau Jaya’s villagers in Work Area of SiakHulu I’s Public Health Care. The sampling method of technique used was system random sampling with the sample size are 180 people. The analysis used is univariat analysis and bivariat. The chi square test result between knowledge and prevention of dengue obtained p value = 0,003 and POR=5,018, attitude and prevention of dengue obtained p value= 0,004 and POR=2,755, role of health worker and prevention of dengue obtained p value = 0,029 and POR=3,791. Conclusion there are significant relation between knowledge, attitude and role of health worker in the prevention of dengue. Advice to the Public Health Centre are to maximize the provision of health education and participate in promoting 3M program, then monitoring and evaluation in their working area.